The political stability of the state as an indicator of sustainable development (Journal of Philosophy Culture and Political Science, 2018)
Republic of Kazakhstan is one of the steadily developing States in the global political arena. Along with economic growth, domestic political stability is the main condition for sustainable development of the state. The ability to protect national interests in world politics is an indicator of a sovereign state. In today’s world, sustainable development is the highest political value. It is main conditions of the prevention of threats and risks to political stability. It is important to identify the risks and threats to the political stability of the state, correctly identify negative and positive factors of sustainable development. Considered the risks of the political system of Kazakhstan are caused by the implementation of its internal policy. The frequency of occurrence of an event such as parliamentary crisis is the basis for determining the probability of risk. The article describes the risks of the Republic of Kazakhstan’s political system.Key words: political stability, stability, national interests, crisis of power.